CLASS ORGANIZATION: ¿DO I PREPARE MY CLASS TO TEACH OR FOR THE STUDENT TO LEARN? - Viale Tudela, Hector Ernesto (2011)
When we prepare and organize a class, we must not only think about what we say or how to say it. Class organization must transcend the concerns of the dictation. We must incorporate tasks so the students can have an active attitude in class: we must not only develop their intellectual abilities, which correspond to the passive situation of listening to the teacher. We must ensure that in the learning process the student involves other skills that stimulate their cognitive aspect: with this in mind, the teacher takes on a mediating role, giving prominence to the student. We must seek a balance between teacher, student and the tasks or activities designed. In this article, we will reflect on the advantages of having a good class design, which no longer look only at the content that is taught, but it concentrates on teaching how to learn; it no longer the course but the student is the center of the teaching-learning system. It will no longer be a knowledge-based training, but a comprehensive training that addresses a variety of competencies.